ChemInform Abstract: Diversity‐Oriented Synthesis of Pyrazolo[4, 3‐b]indoles by Gold‐Catalyzed Three‐Component Annulation: Application to the Development of a New Class of CK2 Inhibitors. Issue 39 (5th September 2013) - Hou, Zengye; Oishi, Shinya; Suzuki, Yamato; Kure, Tatsuhide; Nakanishi, Isao; Hirasawa, Akira; Tsujimoto, Gozoh; Ohno, Hiroaki; Fujii, Nobutaka
Abstract A variety of pyrazolo[4, 3‐b]indoles is prepared via a gold‐catalyzed three‐component annulation of alkynes (I) with hydrazine derivatives (II) and carbonyl compounds (III) followed by an intramolecular C‐H amination of resulting dihydropyrazoles (IV).